A feasibility study in the development of an off-line PLC based robot control system - Bryson, Craig Weir (My University, 1990)
Robotics are becoming a more prominent force in the industrial environment, and research is being concentrated on control rather than on the robot. The feasibility of a substitute, off-line, plc based control system was investigated. Many advantages are associated with an off-line system, as well as the large financial saving (at the most 50% that of the existing controller) . A PLC with discrete 1/0 modules and a fast counting module were used. Open loop control was looked at, with optical encoders used for position control. Overshoot of the DC motors consistently occurred, and other external factors ensured the unpredictability and instability of open loop control. It was concluded that closed loop control was necessary to ensure accurate positioning and speed control. PLC modules Were investigated, and an axis control system (not yet commercially available) was found to ideally suit the purpose of servo/encoder control. This system makes use of speed and position feedback signals, essential for accurate terminal Control of the robot.
A project report submitted to the Faculty of Engineering, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, University of the Witwatersrand. Johannesburg 1990.
Keywords: Robotics--Research--South Africa